2020
DOI: 10.1002/ijc.33050
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of p38 kinase impedes the mobilization of protumorigenic myeloid populations to impact breast cancer metastasis

Abstract: Patients with metastatic breast cancer (MBC) have limited therapeutic options and novel treatments are critically needed. Prior research implicates tumor‐induced mobilization of myeloid cell populations in metastatic progression, as well as being an unfavorable outcome in MBC; however, the underlying mechanisms for these relationships remain unknown. Here, we provide evidence for a novel mechanism by which p38 promotes metastasis. Using triple‐negative breast cancer models, we showed that a selective inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
(215 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, non-canonical p38α activation in T cells promotes an inflammatory state that facilitates pancreatic ductal carcinoma development 228 . In addition, cancer cells also rely on p38α to produce cytokines and chemokines that recruit pro-tumorigenic myeloid cells to the tumour niche 229 . Similarly, the p38α–MK2 axis was implicated in the upregulation of T cell inhibitory protein PDL1 in cancer cells favouring immune suppression signalling 71 .…”
Section: Physiopathological Functions Of P38αmentioning
confidence: 99%
“…Furthermore, non-canonical p38α activation in T cells promotes an inflammatory state that facilitates pancreatic ductal carcinoma development 228 . In addition, cancer cells also rely on p38α to produce cytokines and chemokines that recruit pro-tumorigenic myeloid cells to the tumour niche 229 . Similarly, the p38α–MK2 axis was implicated in the upregulation of T cell inhibitory protein PDL1 in cancer cells favouring immune suppression signalling 71 .…”
Section: Physiopathological Functions Of P38αmentioning
confidence: 99%
“…p38 inhibition improves not only the persistence and tumor infiltration of T cells that results in their boosted antitumor activity but also enhances the functionalities of gene-engineered T cells (with TCR or CAR) [ 159 ]. Moreover, the p38 kinase inhibition increases the abundance of cytotoxic CD8 + T cells and their tumor infiltration [ 160 ]. miRNA-5119 expressing DCs downregulate PD-L1 and not only prevent exhaustion of CD8 + T cells but also restore the antitumor activity of exhausted T cells and increase their proliferation [ 161 ].…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…The prevention and treatment of cancer metastasis remain to be a great challenge. Pharmacological inhibition of p38MAPK may suppress the metastasis of breast cancer and melanoma 46 , 47 . The oral p38MAPK inhibitor ralimetinib (LY2228820) has undergone clinical trials and demonstrated acceptable tolerability 48 .…”
Section: Discussionmentioning
confidence: 99%